Effect of single-pass friction stir processing parameters on the microstructure and properties of 2 mm thick AA2524 - Jiangmei He; Yijie Hu; Youping Sun; Wangzhen Li; Guojian Luo (Materials Research Express, 2022)
Friction stir processing (FSP) is an important method for obtaining fine grains. To determine the effects of FSP and processing parameters on the microstructure and mechanical properties of rolled sheets, we performed single-pass FSP of a 2 mm thick 2524 aluminium alloy (AA2524) rolled sheet by comparing the combination of different processing parameters. The results show that lamellar grains (rolled state) are replaced by fine dynamic recrystallisation in the stir zone (SZ), and more Al _2 CuMg phases are precipitated simultaneously. As the rotation speed increases, the grain size and width of the pin stir zone (PSZ) increase, the microhardness first decreases and then increases; with the traverse speed increase, the grain size first decreases and then increases, and the width of the PSZ and microhardness decrease. The SZ has the smallest grain size, highest high-angle grain boundaries (HAGBs, with misorientation angles ( θ ) >15°) ratio, and largest ultimate tensile strength (UTS), when the rotation and traverse speed were 1000 r·min ^−1 and 125 mm·min ^−1 , are 1.59 ± 0.82 μ m, 0.91 and 451.23 ± 0.52 MPa, respectively, and the elongation to fracture is 13%. The UTS and elongation were only 95.12% and 98.48% of those of the base metals (BM), respectively, because of the significant decrease in the dislocation density. Fracture analysis revealed ductile fracture of the joint due to the large number of dimples and fine second-phase particles.